CS1 & CS2 curriculum recommendations: Learning from the past to try not to rediscover the wheel again - Sobral, Sónia Rolland (2020)
Initial programming curricular units are of great importance to computer courses. There has been very important work with curriculum recommendations, notably those from Association for Computing Machinery (ACM) and later ACM in conjunction with the Institute of Electrical and Electronics Engineers (IEEE): so far almost twenty curriculum recommendations have been published. Computing is a constantly evolving area, as is society and the way new generations learn. Why are so many recommendations needed? And what are the developments in these recommendations? This article lists initial course units that are suggested or used as examples in each of the curriculum recommendation reports, both initial and generic, and those that address a specific area, namely Computer Engineering (CE), Computer Science (CS), Information Systems (IS), Information Technology (IT), and Software Engineering (SE). This study is of great importance for those who have the responsibility to design and redesign curricula as it points out a number of different paths, namely in relation to the already mentioned distinction by areas but also the distinction that is made by university size, previous knowledge of the students, and also duration of studies, among other variables. Knowing history makes it possible to understand the present and even make better choices for the future.